Papel do sistema nervoso simpático na regulação da massa muscular e hiperalgesia em um modelo murino de fibromialgia - Silva, Raquel Prado da (2023)
Fibromyalgia (FM) is primarily characterized by symptoms such as chronic generalized musculoskeletal pain, along with loss of strength and muscle mass. Furthermore, alterations in Sympathetic Nervous System (SNS) activity have been described in FM patients, which is known to regulate nociceptive mechanisms and muscle plasticity. However, the role of the SNS in the regulation of hyperalgesia and skeletal muscle mass during FM is not well understood. Therefore, in this study, we indirectly evaluated sympathetic activity by quantifying catecholamines, adrenaline and noradrenaline, as well as adrenergic signaling in the soleus muscles of female rats subjected to an FM model induced by double intramuscular injection of acid saline. It was observed that after 7 days of FM induction, there was diffuse hyperalgesia, confirmed by a decrease in the paw withdrawal threshold, and reductions in muscle mass and strength, which were associated with attenuation of adrenergic signaling measured by the content of phosphorylated proteins by the cAMP-dependent kinase (PKA) and its target proteins. Based on these results, it was demonstrated that treatment with clenbuterol (β2-adrenergic receptor agonist) attenuated hyperalgesia and muscle atrophy in FM animals. To confirm that the decrease in catecholamine release was not specific to the acid saline injection-induced hyperalgesia model, a second experimental FM protocol was conducted with intramuscular administration of carrageenan. As expected, carrageenan induced a decrease in paw withdrawal threshold and plasma adrenaline concentration, although it did not induce muscle atrophy. Since both FM models used in this study were able to reduce adrenal catecholaminergic secretion, it was postulated that adrenaline depletion through bilateral removal of adrenal medulla (ADM) could mimic FM symptoms. Indeed, ADM induced mechanical hyperalgesia and increased muscle proteolysis in animals maintained under basal conditions. Taken together, the results demonstrate that the SNS is involved in the control of nociception and muscle plasticity in an experimental model of FM and support clinical studies aimed at treating FM patients.